Impact of biogenic very short-lived bromine on the Antarctic ozone hole during the 21st century - Fernandez, Rafael Pedro; Kinnison, Douglas E.; Lamarque, Jean Francois; Tilmes, Simone; Saiz-lopez, Alfonso
Active bromine released from the photochemical decomposition of biogenic very short-lived bromocarbons (VSL_Br ) enhances stratospheric ozone depletion. Based on a dual set of 1960-2100 coupled chemistry-climate simulations (i.e. with and without VSL Br ), we show that the maximum Antarctic ozone hole depletion increases by up to 14% when natural VSLBr are considered, in better agreement with ozone observations. The impact of the additional 5 pptv VSL Br on Antarctic ozone is most evident in the periphery of the ozone hole, producing an expansion of the ozone hole area of ~5 million km 2 , which is equivalent in magnitude to the recently estimated Antarctic ozone healing due to the implementation of the Montreal Protocol. We find that the inclusion of VSL Br in CAM-Chem does not introduce a significant delay of the modelled ozone return date to 1980 October levels, but instead affect the depth and duration of the simulated ozone hole. Our analysis further shows that total bromine-catalysed ozone destruction in the lower stratosphere surpasses that of chlorine by year 2070, and indicates that natural VSL Br chemistry would dominate Antarctic ozone seasonality before the end of the 21 st century. This work suggests a large influence of biogenic bromine on the future Antarctic ozone layer. Fil: Fernandez, Rafael Pedro. Consejo Superior de Investigaciones Científicas. Instituto de Química Física; España. Universidad Tecnologica Nacional. Facultad Regional Mendoza. Secretaría de Ciencia, Tecnología y Postgrado; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza; Argentina Fil: Kinnison, Douglas E. National Center For Atmospheric Research. Amospheric Chemistry División; Estados Unidos Fil: Lamarque, Jean Francois. National Center For Atmospheric Research. Amospheric Chemistry División; Estados Unidos Fil: Tilmes, Simone. National Center For Atmospheric Research. Amospheric Chemistry División; Estados Unidos Fil: Saiz-lopez, Alfonso. Consejo ...